PENGARUH PERMAINAN MELEMPAR DAN MENANGKAP BOLA TERHADAP PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI KELOMPOK B1 TK BHAYANGKARI BAGANSIAPIAPI - Lisa, Lisa; Zulkifli, Zulkifli; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Learning activities conducted in kindergarten Bhayangkari only considers the activities of reading, writing, and arithmetic are important so that the child's gross motor skills are still low, it is seen from the attitude of the child's behavior was not interested and less active in participating in learning gross motor skills. This study aims to determine through throwing and catching a ball game can see the influence of children's ability to improve gross motor skills of children and measure how high the increase in children before and after treatment with experimental methods, as well as to find a creative way in creating a fun learning environment to improve skills physical motor skills of children. The method used is ekprimen held in May 2015. The number of children in this study were 20 people, consisting of 11 boys and 9 girls. Based on data from the percentage after given treatment with a score of 82.91%, while the influence of gross motor skills of children before and after treatment equal to 34.37% and concluded that with the activities of throwing and catching the ball influential improve gross motor skills in children aged 5 -6 years in kindergarten Bhayangkari Bagansiapiapi. Keyword : Rough Motoric ability , throwing and catching a ball game.